ASA 2022 Data-Driven Decision Making Book of short papers - Cavalletti, Barbara; DI BELLA, ENRICO; Fabbris, Luigi; Lagazio, Corrado (Proceedings e report, 2023)
This volume collects the contributions presented at the conference "Data-driven Decision Making" organized by the Italian Association for Applied Statistics, held in Genoa from 12 to 14 September 2022. The papers cover a broad range of topics, with a common thread: the use of statistical methods to support decision-making both in public administrations and in private companies.